2016
DOI: 10.1186/s12877-016-0228-z
|View full text |Cite
|
Sign up to set email alerts
|

Case finding for sarcopenia in geriatric inpatients: performance of bioimpedance analysis in comparison to dual X-ray absorptiometry

Abstract: BackgroundSarcopenia is a common geriatric syndrome associated with serious adverse health outcomes. The European Working Group on Sarcopenia in Older People (EWGSOP) suggests different methods for case finding for sarcopenia. However, data comparing the different methodological options are scarce for geriatric inpatients.MethodsOn the basis of the recommendations of the EWGSOP sixty geriatric inpatients underwent measurement of gait speed, hand grip strength and muscle mass by both, dual X-ray absorptiometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…Moreover, reference values have been established for older individuals [ 3 ]. Even if the method’s accuracy has been challenged and has been reported to overestimate muscle mass and underestimate fat mass [ 52 54 ], it is possible to use some adjustment equations to obtain valid measurements [ 55 ]. In summary, we would propose assessing primarily muscle mass by DXA, if this tool is available, and if not, anthropometry measurements can easily be used, in primary care settings, as a first screening of patients with low muscle mass.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, reference values have been established for older individuals [ 3 ]. Even if the method’s accuracy has been challenged and has been reported to overestimate muscle mass and underestimate fat mass [ 52 54 ], it is possible to use some adjustment equations to obtain valid measurements [ 55 ]. In summary, we would propose assessing primarily muscle mass by DXA, if this tool is available, and if not, anthropometry measurements can easily be used, in primary care settings, as a first screening of patients with low muscle mass.…”
Section: Resultsmentioning
confidence: 99%
“…We also showed that low muscle mass was present in 35% of the participants according to BIA, while this was 100% according to the muscle thickness of the rectus femoris measured with ultrasound. One possible explanation for this discrepancy is that BIA is known to overestimate muscle mass (giving lower prevalence rates of low muscle mass) [65,66]. Where BIA estimates muscle mass, ultrasound measures only the size of one muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, common conditions in hospitalized CVD patients (e.g., peripheral edema, low albuminuria, kidney disease) may lead to erroneous BIA results [46,47].…”
Section: Discussionmentioning
confidence: 99%